Plasma dipeptidyl peptidase IV activity and measures of body composition in apparently healthy people. Issue 4 (April 2016) - Neidert, Leslie E.; Wainright, Katherine S.; Zheng, Chen; Babu, Jeganathan Ramesh; Kluess, Heidi A.
Abstract: Aim: Based on its regulatory action on glucagon-like peptide 1, dipeptidyl peptidase IV (DPP-IV) has increasingly been linked to Type 2 diabetes. However, there is no evidence as to how this normal modulatory enzyme leads to pathology. It is thought that DPP-IV is affected by the development of obesity, which is a common precursor to Type 2 diabetes. Little is known about the relationship between DPP-IV activity in plasma and specific body composition measures. Main methods: In the current study, plasma DPP-IV activity and body composition measures were collected from 111 healthy subjects between the ages of 19 and 70 years old for analysis. Key findings: The mean plasma DPP-IV activity was 35.9U/L ± 12.3, falling within normal reference value range presented by Durinx et al. DPP-IV activity was negatively correlated with absolute body fat mass, but absolute lean mass was positively correlated. Consistent with the findings, DPP-IV activity was also negatively correlated with absolute gynoid fat (p = 0.0047). DPP-IV activity did not have a significant correlation with absolute android fat mass, visceral adipose tissue, BMI, and age. Significance: From these results, it can be concluded that high activity of DPP-IV is not indicative of pathology, and specific body composition components may influence soluble DPP-IV activity in the blood.